2023
DOI: 10.1007/s11764-023-01366-5
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and enablers to participation in physical activity among women diagnosed with ovarian cancer

Abstract: Purpose Ovarian cancer is the leading cause of death among gynecological cancers, with low survival rates and a high disease burden. Despite the known benefits, most women reduce their participation in physical activity following diagnosis. Little is known about ovarian cancer survivors’ experiences of physical activity. The primary aim of this study was to explore the barriers and enablers to participation in physical activity among women diagnosed with ovarian cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Twenty-three studies contributed to the theory that dedicated survivorship staff can ensure that survivors receive quality survivorship information that addresses their needs. 22,24,25,27,[33][34][35][36][37][38]41,42,[44][45][46][47][48][49][50][51][52][53][54] In several studies, healthcare professionals reported that due to their high caseloads and competing priorities, limited time is dedicated to the provision of survivorship information; particularly at times where the survivor is undergoing active treatment and communications tend to focus on clinical issues. 24,33,37,50 Crawford-Williams and colleagues examined experiences of rural Australian cancer survivors and found that due to the limited consultation time dedicated to survivorship, survivors experienced difficulties in processing and retaining this information and felt their emotional needs were overlooked.…”
Section: Theory 2: Enhance Communication Among Care Teamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty-three studies contributed to the theory that dedicated survivorship staff can ensure that survivors receive quality survivorship information that addresses their needs. 22,24,25,27,[33][34][35][36][37][38]41,42,[44][45][46][47][48][49][50][51][52][53][54] In several studies, healthcare professionals reported that due to their high caseloads and competing priorities, limited time is dedicated to the provision of survivorship information; particularly at times where the survivor is undergoing active treatment and communications tend to focus on clinical issues. 24,33,37,50 Crawford-Williams and colleagues examined experiences of rural Australian cancer survivors and found that due to the limited consultation time dedicated to survivorship, survivors experienced difficulties in processing and retaining this information and felt their emotional needs were overlooked.…”
Section: Theory 2: Enhance Communication Among Care Teamsmentioning
confidence: 99%
“…Eleven studies contributed to the generation of this theory on the importance of providing multiple modalities of survivorship information. 28,30,31,34,35,41,42,51,54,60,62 Consultations with healthcare professionals, either in-person or phone-based, are valued and regularly utilized by cancer survivors. 30,35,41,42 Indeed, in the study by Herrmann and colleagues, some cancer survivors suggested providing face-to-face information and support sessions at multiple geographical locations to improve accessibility.…”
Section: Theory 6: Provide Survivorship Information In Multiple Modal...mentioning
confidence: 99%